A model to examine the influence of perceived security and trust to adopt mobile banking in the United Arab Emirates - Elhendy, Mahmoud Mohamed Mahmoud (2025)
For years, mobile banking adoption behaviour has received much attention from academic scholars. Users are frequently sceptical of m-banking security due to an increasing trend of cyber-attacks. Also, there is a scarcity of research in the United Arab Emirates (UAE), particularly where security-related issues have been identified as one of the barriers that prevent bank customers from adopting m-banking. Thus, this study is conducted to investigate the factors of m-banking adoption intention. This study is extending the Unified Theory of Acceptance and Use of Technology (UTAUT) by developing a model that incorporates perceived security as moderator factor and trust as independent factor with other UTAUT factors to predict m-banking adoption intention in the UAE. The data was collected from 239 m-banking users in the UAE using a web survey technique and the Partial Least Square (PLS) method to validate the research model and test the hypotheses. The study used non-probability sampling because the researcher could not establish the sampling frame due to privacy issues, as banks cannot disclose the data of their customers who are using mobile banking. The non-probability sampling technique used here is convenience sampling due to its simplicity, low cost, and availability. The results showed that performance expectancy, effort expectancy, trust, and perceived security positively influenced m-banking adoption intention. Additionally, perceived security was found to be positively moderating these relationships. However, the results showed insignificant statistical support explaining the relationship between social influence and users’ intention to adopt m-banking. In conclusion, this study theoretically contributed to the body of knowledge by identifying the significant factors that influence m-banking adoption intention in the UAE. Additionally, this study demonstrated that perceived security is an important moderating variable and trust, as an independent factor, is also one of the important factors influencing users’ intention to adopt m-banking. Practically, this study contributed by suggesting mechanisms and strategies that will help banks promote the adoption of m-banking.